2011
DOI: 10.1017/s0007114511003394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pomegranate extracts on cartilage, bone and mesenchymal cells of mouse fetuses

Abstract: Pomegranate is a rich source of polyphenols, which are believed to be responsible for the oestrogenic activities of extracts of this fruit in mice. One of these potential activities is the prevention of bone loss. The objectives of the present study were to determine the effects of pomegranate extract on chondrogenesis and osteogenesis in mouse embryos in vivo and limb bud cultures in vitro. A total of fifty pregnant Balb/c mice were given vehicle, pomegranate juice extract (PJE), pomegranate husk extract (PHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Histopathological analysis indicated a reduction in joint infiltration by inflammatory cells ( 23 ) . Pregnant mice fed pomegranate fruit or husk extracts between days 8 and 18 of gestation showed increased Ca content in the pregnant mice as well as increased femur length and indices of osteogenesis in the embryos ( 24 ) . Purified ellagic acid has also been shown to stimulate mineralisation of extracellular matrix by the osteoblastic cell line, KS483 cells, similar to that of 17β-oestradiol ( 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological analysis indicated a reduction in joint infiltration by inflammatory cells ( 23 ) . Pregnant mice fed pomegranate fruit or husk extracts between days 8 and 18 of gestation showed increased Ca content in the pregnant mice as well as increased femur length and indices of osteogenesis in the embryos ( 24 ) . Purified ellagic acid has also been shown to stimulate mineralisation of extracellular matrix by the osteoblastic cell line, KS483 cells, similar to that of 17β-oestradiol ( 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study with rabbits showed that the consumption of PFE significantly reduced the expression of IL-6, MMPs, and PGE 2 , while the expression of AGC and COL2A1 was upregulated [113]. Furthermore, in vivo studies in mice have shown that the ingestion of PFE suppresses inflammation and joint destruction in a model of collagen-induced arthritis (CIA) [110], prevents the dose-dependent negative effects of iodoacetate [114], and exerts a significant chondroinductive potential on mouse embryos in vivo and limb bud cultures in vitro, with increased cell proliferation and differentiation rates [115]. In patients, the intake of PFE resulted in improved physical function, the reduced degradation of cartilage enzymes, and the increased anti-oxidant status in patients with knee OA [116].…”
Section: Pomegranatementioning
confidence: 99%
“… Monsefi et al (2012) reported that embryo femur length increased following treatment of mice with PJ extract (an in-house prepared PJ extract, administered at 3.3 ml/kg between days 8 and 18 of pregnancy), and that PJ increased cell proliferation and differentiation in vitro , consistent with a positive effect of PJ on bone cells. However, a bone growth-promoting effect of PJ (administered from E12.5) was not evident in the current study, as PJ did not affect crown rump length.…”
Section: Discussionmentioning
confidence: 94%